Teacher–student interaction, empathy and their influence on learning in swimming lessons. Issue 8 (16th November 2016) - Lémonie, Yannick; Light, Richard; Sarremejane, Philippe
Abstract : The bulk of interest in the role that interaction plays in learning in sport and physical education (PE) has focused on peer interaction at the expense of teacher–student interaction. This article redresses this imbalance in the literature by reporting on a study that inquired into the nature of teacher–student interaction and its effect on learning in PE swimming lessons in a French secondary school. Informed by an enactivist conceptualisation of learning, it emphasises the subjective dynamics of interaction to suggest that patterns of coordination should not be seen as being predetermined and determining student learning but, instead, as forms of engagement that influence, and are influenced by, the dynamics of interaction. In doing so it suggests the pivotal importance of teacher empathy for student learning through interaction in PE.